Betting against beta strategy in other asset pricing anomalies - You, Shuangmeng (2020)
The beta anomaly, known as high (low) beta stocks always produce low (high) abnormal returns, is one of the main challenges to the traditional Capital Asset Pricing Model (CAPM). Inspired by the betting against beta strategy proposed by Frazzini and Pedersen (2014), we consider the long-short, zero-cost portfolios based on the documented asset pricing anomalies, including momentum (MOM), return volatility (VOL) and idiosyncratic volatility (IVOL). As beta estimation is a key part of the empirical process, we apply three different methods to each strategy separately. Then, we use the elimination method and the beta-ranking weighted method in order to mitigate long-short anomaly portfolios’ exposure to the beta anomaly. Furthermore, we exploit the double sorts on beta and other asset pricing anomalies in the bid of investigating if the low-beta anomaly can explain the abnormal returns to other documented asset pricing anomalies. In addition, we add BAB factor as an explanatory variable in the traditional CAPM. Both the double sorts and regression tests present compelling evidence that the beta anomaly can explain part of the abnormal returns to other asset pricing anomalies. In all, it is concluded that the magnitude of this explanatory power varies both on the basis of pre-formation beta estimation technique and beta mitigation method.